PENERAPAN METODE ROLE PLAY UNTUK MENINGKATKAN PEMAHAMAN PEMBELAJARAN SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI MUSYAWARAH DI SDN 01 NAMBANGAN KIDUL KOTA MADIUN - Lusiyanti, Fitria; Mersina Mursidik, Elly's; Zahro, Fakhriyatu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance the understanding of the concept of musyawarah (deliberation) among fourth-grade students at SDN 01 Nambangan Kidul through the implementation of the role-play method. The background of the study is the low participation of students in discussions and decision-making processes, attributed to the use of conventional teaching methods. This Classroom Action Research (CAR) was conducted in two cycles with 13 student participants. Data were collected through observations of teacher and student activities and evaluation tests. The results showed that the role-play method effectively improved student understanding. In the first cycle, student involvement was low due to insufficient understanding of their roles in the simulation and unclear teacher instructions. After improvements were made in the second cycle, there was a significant increase in student participation, confidence in expressing opinions, and understanding of the musyawarah concept. The average score improved from 71.15 to 83.08, and classical completeness reached 92.31%. Thus, role play has proven to be effective in improving student learning outcomes on the topic of musyawarah